Spirituality and quality of life among university students during Covid-19 pandemic - Ab Razak, Ratna Roshida; Sanusi, Zainal Abidin; Mohd Yusoff, Ahmad Nasir; Mohd Isa, Nur Ayuni (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
This research is aimed to examine the quality of students’ life during the COVID-19 pandemic. In other words, we want to explore how much spiritual wisdom the students possess which enables them to successfully face the catastrophe. To measure the quality of student life, WHOQoL-BREF questionnaire which is short questionnaire consists of 26 items version of World Health Organization Quality of Life assessment (WHOQoL-100), with some amendments, will be employed. The scope of this cross-sectional study is confined to students who are taking university courses in semester 2, 2019/2020, with the total of 160 samples. This research is considered important because spirituality not only allows humans to respond appropriately in a specific circumstance or scenario, but also to analyze why they are in that state, and how they can adapt, accept and adjust to the situation. Spirituality is the intelligence of the soul, the wisdom with which we can heal ourselves and make ourselves whole, full of sense, intent and value, particularly in times of pandemic, adversity and uncertainty like COVID-19 in relation to the link between superpower, oneself, others and nature.